Effects of the COVID-19 global crisis on the working capital management policy: Evidence from Poland - Grzegorz Zimon; Hossein Tarighi (Journal of Risk and Financial Management, 2021)
The paper aims to investigate the effects of the COVID-19 pandemic on working capital management policies among Polish small and medium-sized enterprises operating in Group Purchasing Organizations (GPOs). The results show that the firms adopted a moderate-conservative strategy for their working capital management. Moreover, the evidence confirms that the COVID-19 pandemic crisis did not change Working Capital Management (WCM) strategies significantly. The companies that have high financial security as a result of the high ratio of Liquidity, Quick, and cash conversion cycle (CCC) have tried to attract more new customers in the market by increasing the due date of accounts receivable so they can improve their sales performance, and also reduce the liabilities turnover to be able to work with more suppliers in the market. Moreover, among the various WCM strategies, the companies with a higher CCC ratio, along with those whose bulk of current assets consisted of accounts receivable and short-term investments, managed to have higher sales returns. Finally, our outcomes indicate that the firms operating in large cities have lower sales returns, meaning even Polish small and medium-sized enterprises' ability within GPOs with the aid of the central unit can also get high return on sales (ROS) results.
Keywords: 330; COVID-19 pandemic; group purchasing organizations; Poland; SMEs; working capital